Analisis Solutif Kerjasama Orang Tua Dan Guru Dalam Meningkatkan Motivasi Belajar Peserta Didik Di MI Dlauul Islam - Qiptiyah, Mariyah; Mamluatun Ni’mah; Farich Purwantoro (Universitas Yudharta Pasuruan, 2024)
The purpose of this study is to determine the nature of parent-teacher cooperation and the factors that influence parent-teacher cooperation in increasing students' motivation to learn at MI Dlauul Islam Brumbungan Lor. In this study, the researchers used a descriptive qualitative approach with data collection using interview, observation and documentation techniques. The interview samples used in this study were the principal of the madrasa, parents of the students and the fourth grade teacher. Data analysis in this study is done in three ways, namely data reduction, data presentation and data verification. Based on the results of data analysis obtained, it shows that the form of cooperation between parents and teachers in increasing students' learning motivation, namely, the institution maintains good communication with parents of students, forms a committee in the madrasa, there is mutual trust between parents and teachers in providing supervision to students, the madrasa always involves parents in madrasa activities, holds regular meetings in the madrasa at the end of each semester as a form of evaluating the shortcomings of each student. Factors influencing parent-teacher collaboration due to low student motivation to learn.